Determination of rivaroxaban by different factor Xa specific chromogenic substrate assays: reduction of interassay variability - Harenberg, Job; Krämer, Roland; Giese, Christina; Hetjens, Svetlana; Weiß, Christel; Wehling, Martin (Journal of thrombosis and thrombolysis, 2011)
Rivaroxaban and other oral direct factor Xa inhibitors (ODiXa) are currently developed for prophylaxis and treatment of thromboembolic diseases using fixed doses. Although routine monitoring is not required, assessing the intensity of anticoagulation may be useful under certain clinical conditions. ODiXa prolong coagulation times of several clotting assays and, thus, their concentration may be determined in factor Xa specific chromogenic substrate assays. So far, no standardized and validated assay is commercially available. Here, five methods (A through E) are studied and optimized to reduce interassay variability. Human pooled plasma was spiked by a serial dilution of rivaroxaban (25-900 ng/ml). The release of para-nitroaniline from the chromogenic substrates was measured by the optical density (OD) at 405 nm. Method B was identified to yield the lowest sum of deviations from the mean value of the OD concentration curve calculated from all assays. Spline functions were developed for OD versus concentration curves for all methods. The calculated OD versus concentration curves overlapped for all methods. The coefficient of variation for all assays and concentrations of rivaroxaban decreased from 25.3 ± 11.4% using the original data to 3.8 ± 2.2% using the calculated data (P < 0.0001). The robustness of the chromogenic assay (method B) remains to be corroborated in interlaboratory comparisons.